A Supervised Learning Approach to Entity Search - Hu, Guoping; Liu, JJ (Jingjing); Li, Hang; Cao, Yunbo; Nie, Jian-Yun; Gao, Jianfeng (AIRS 2006, 2006)
In this paper we address the problem of entity search. Expert search and time search are used as examples. In entity search, given a query and an entity type, a search system returns a ranked list of entities in the type (e.g., person name, time expression) relevant to the query. Ranking is a key issue in entity search. In the literature, only expert search was studied and the use of co-occurrence was proposed. In general, many features may be useful for ranking in entity search. We propose using a linear model to combine the uses of different features and employing a supervised learning approach in training of the model. Experimental results on several data sets indicate that our method significantly outperforms the baseline method based solely on co-occurrences.